Characterization and effect of Azotobacter, Azospirillum and Pseudomonas associated with Ipomoea Batatas of Colombian Caribbean - Jazmín Vanessa Pérez-Pazos; Diana Beatriz Sánchez-López (Revista Colombiana de Biotecnología, 2017)
The use of plant growth promoting Rhizobacteria (PGPR) is an alternative to replace chemical fertilizers for the cultivation of agricultural crops. The aim of this research was to search, selection and characterization of PGPR from the genus Azotobacter, Azospirillum and Pseudomonas natives from sweet potato (Ipomoea batatas) plants and rhizosphere of representative production regions of the Colombian Caribbean. Selected isolates were identified by molecular methods and they were screened in vitro for activities related to plant growth such as phosphate solubilization, indole production and acetylene reduction. The strains were tested in the greenhouse on plants of Ipomoea batatas produced in vitro. The height, root length, dry mass of the shot and root were evaluated. Associated with sweet potato crop us finded strains identificated as Azotobacter vinelandii, Azotobacter chroococcum, Azospirillum lipoferum, Azospirillum brasilense and Pseudomonas denitrificans. The strains were able to solubilize phosphate, synthesize indole-3-acetic acid (IAA) and reduce acetylene. The inoculation of bacteria selected increased growth parameters such as root length, height, dry weight root and shoot in plants of sweet potato in greenhouse. Those results catalog to the isolated obtained as possible microorganisms with potential as biofertilizers in sweet potato.